2005
DOI: 10.1111/j.1654-109x.2005.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of Calluna vulgaris regeneration after burning of coastal heath in central Norway

Abstract: Questions: How does Calluna vulgaris regenerate after burning wet and dry heaths of different age? Location: Central Norway. Methods: Patches of Calluna dominated old and young wet heath and old dry heath were burned. The mean temperatures reached in the categories of heath were measured. Cover, frequency, height and number of seedlings of Calluna were studied in plots. Results: The mean burning temperatures varied from 680 to 740°C, and were highest in wet heath that had not been burned for at least 50 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…The effectiveness of fire management for the restoration of degenerated Calluna thus depends on the establishment of seedlings, which is additionally determined by characteristics of the implemented fires themselves (such as duration and temperatures), post‐fire substrate type or soil moisture (Whittaker and Gimingham ; Grant ; Nilsen et al. ; Matt Davies et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of fire management for the restoration of degenerated Calluna thus depends on the establishment of seedlings, which is additionally determined by characteristics of the implemented fires themselves (such as duration and temperatures), post‐fire substrate type or soil moisture (Whittaker and Gimingham ; Grant ; Nilsen et al. ; Matt Davies et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…one ewe per 2 ha) graze year‐round in the study area. In the study area, vegetative regeneration from Calluna has been shown to be absent in young as well as old Calluna stands (Nilsen et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Minimum distance between blocks was set at 20 m. Fires were set between February and April under appropriate weather conditions, i.e. sufficient wind to carry the fire onwards and with frozen or wet ground (the mean fire temperatures range from 680 °C to 740 °C, see Nilsen et al 2005). Within each block, two 1‐m 2 plots were placed randomly and permanently marked with metal poles, avoiding marked depressions and concavities and areas with >10% bare rock or bare soil, >20% faeces, <4 m from edge of burned area or adjacent to another plot, and incompletely burned vegetation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations